Nilai Karakter Religius Pada Ekstrakurikuler Rebana di SD Muhammadiyah 11 Semarang - Candra Gunawan; Mei Fita Asri Untari; Eka Sari Setianingsih (Universitas Ngudi Waluyo, 2020)
Character education is a noble cultivation of character which cannot be separated in the perfection of life. Character education is one of the efforts to instill noble character values in order to become a good person. It can be seen that the cultivation of this noble character is the foundation of the nation's character. But in fact that the character of the present era is in a phase of concern. This can be seen in many problems that focus on the loss of noble character that is not well named. So it is necessary to instill character early on through family, school, community and government. One of them is through religion which is very closely related to religious character. Which can be embedded either in spiritual activities, habituation through anything, for example with tambouric extracurricular. Therefore, researchers try to analyze any religious character that is embedded in the extracurricular. Therefore, this study analyzes the character contained in tambouric extracurricular with a focus on religious character in Muhammadiyah 11 Elementary School Semarang. Where the character values have 5 aspects, namely aspects of belief, aspects of worship, aspects of appreciation, aspects of knowledge, aspects of experience. Therefore, researchers use a qualitative approach. In this study using data collection techniques that are needed is by observation, interview and documentation. Based on the results of research that students have addressed aspects of religious character through tambourine extracurricular activities and habituation at SD Muhammadiyah 11 Semarang.